Grade 10 teachers’ perceptions of their application of socio-cultural and multiple intelligences on English second language learners - Ndu, Onyinyechi Glory; Tshotsho, Baba Primrose; Cekiso, Madoda (Journal for Language Teaching, 2022)
In multilingual or multi-cultural settings, teachers must be sensitive to the diverse intelligence of learners for teaching and learning to have impact and be beneficial to them. Low performance and the resultant academic failure among high school learners specifically in South Africa, and inability to manage diverse learning abilities have necessitated the search for a unique way to accommodate the learning differences found in the classroom. The study focused on learners’ differences and supports implementation of differentiated instruction. Fewer studies exist on English Second Language (ESL) rural high school teachers’ perceptions of the application of socio-cultural and multiple intelligences, and on the diverse ESL learners taught to ascertain the scope of the need for teacher training in differentiated instruction in rural South Africa. Data were drawn from fifty teachers in grade ten using a questionnaire. The study revealed that it is challenging for teachers to determine learners’ intelligences and emotional needs. 66% (n=33) of the teachers agreed to accommodate students of different learning abilities, 34% (n=17) considered learners’ gender differences, and 62% (n=31) considered learners’ cultural backgrounds and adopted group learning. The study mainly recommends training and supervision on the strategies for gender differences and accommodation for diverse learning abilities.